Atmospheric scattering - state of the art - Lopes, Diogo A. R. (2014)
Atmospheric scattering is the natural phenomenon mainly responsible for the colours we observe in the sky. Over the years, several realistic computer graphics algorithms have been proposed in order to reproduce these colours. This state of the art is motivated by the large amount of scattered information, and by its great potential usage in a wide range of applications like flight simulators, video games and movies. This paper will cover the most important models and will present their evolution over the years. The first part contains a small introduction to the mechanics behind the light scattering phenomena. The second part will cover the earlier models, very much focused in the physical phenomenon. The third section will cover GPU based models, more focused on performance.